2016
DOI: 10.4103/0975-1475.186369
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of mandibular ramus for gender estimation: Retrospective study

Abstract: Background and Aims:Gender estimation is a very important part of a study in the field of anthropology and forensic sciences. In the skeleton, gender estimation is the first step of the identification process as subsequent methods for age and stature estimation are sex-dependent. Skeletal components such as the pelvis and skull are investigated for gender estimation and the mandible is a practical element to analyze sexual dimorphism in fragmented bones. The aim of the present study is to measure, compare, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
42
6
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 10 publications
9
42
6
5
Order By: Relevance
“…The main issue in forensic anthropology is human identification, most often of human remains [1]. Sex deter-mination is the first step of personal identification in the field of forensics and is essential for reconstructive profiling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main issue in forensic anthropology is human identification, most often of human remains [1]. Sex deter-mination is the first step of personal identification in the field of forensics and is essential for reconstructive profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, race, and occlusion status affect the morphological characteristics of the mandible. Studies have shown that remodeling of the mandibular bone occurs with aging [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological characteristics of the mandible show differences in age, sex, dental status, and race [8]. Various skeletal morphological features can be used for sex determination.…”
Section: Introductionmentioning
confidence: 99%
“…Sex identification in bone remnants is important in forensic practice and forensic anthropology. The skull is the most dimorphic portion of skeleton, providing, after the pelvis, an accuracy of up to 92% [1,8]. The GA can be used as a tool in forensic odontology [31].…”
Section: Introductionmentioning
confidence: 99%